Teachers’ Attitudes, Competencies, and Challenges in Inclusive Education Implementation Practices - Gusma Afriani; Aisyah, Siti (Global Education Journal, 2025)
The concept of inclusive education has gained global attention as a means to provide equitable educational opportunities for children with special needs (CWSN) within general school environments. However, the effective implementation of inclusive education remains a challenge, especially in contexts with limited resources and support structures. This study aims to explore the role of teachers in implementing inclusive education and identify the factors that influence their effectiveness in inclusive classrooms. A qualitative research design, employing semi-structured interviews, classroom observations, and document analysis, was used to gather data from twelve teachers across three public elementary schools in [City/Region Name], Indonesia. The findings reveal that teachers' attitudes, professional training, and institutional support play critical roles in shaping the inclusivity of classrooms. Positive teacher attitudes and adaptive teaching strategies were associated with successful inclusion, whereas lack of training and support resulted in minimal inclusion. The study concludes that empowering teachers with adequate training, emotional support, and institutional resources is essential for achieving true inclusion in schools. This research contributes to the growing body of literature on inclusive education by providing insights into the everyday experiences of teachers and the systemic challenges they face. It highlights the need for a more holistic approach to teacher development and school-wide support to bridge the gap between policy and practice.